High-hardness wear-resistant TiAlN / TiSiN superlattice coating and preparation method thereof

By adjusting the target installation position and single-layer coating deposition time to regulate the modulation period and modulation ratio of nano-multilayer coatings, the problems of difficult preparation and insufficient wear resistance of existing superlattice coatings are solved, and coatings with high hardness, high wear resistance and high deposition rate are achieved.

CN119685781APending Publication Date: 2025-03-25CHENGDU TOOL RES INST +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411872613.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing superlattice coating is difficult to prepare and complex to operate, making it difficult to ensure the stability and yield of the coating, resulting in low tool hardness and low wear resistance, which makes it difficult to meet process requirements.

Method used

The nanomultilayer coating with superlattice structure was obtained by adjusting the target installation position and the single-layer coating deposition time to regulate the modulation period and modulation ratio of the nanomultilayer coating.

Benefits of technology

It achieves a denser coating structure, fewer internal defects, higher hardness, better wear resistance, high deposition rate, simple operation, and can meet process needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685781A_ABST
    Figure CN119685781A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of superlattice coatings, and discloses a high-hardness wear-resistant TiAlN / TiSiN superlattice coating which comprises a multi-layer nano-layer structure, and the total thickness of the multi-layer nano-layer coating is 3.7-5.0 microns; the multi-layer nano-layer structure is formed by alternately depositing a TiAlN nano-layer and a TiSiN nano-layer which are of two face-centered cubic structures; the thickness ratio of the TiAlN nano layer to the TiSiN nano layer is 1: 1, and the thickness of a single layer is less than 10nm; the preparation method comprises the steps of substrate pretreatment and deposition treatment, wherein the deposition treatment comprises a substrate heating step, a substrate etching step, a target cleaning step, a nanometer multilayer coating deposition step and a cooling step. The operation method is simple, the deposition rate is high, the coating process is stable, the structure and performance of the coating can be precisely regulated and controlled, the TiAlN / TiSiN nano multilayer coating with the superlattice structure is obtained, the superhard level is achieved, and the hardness and wear resistance of the tool are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of superlattice coating preparation, and in particular to a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating and a preparation method thereof. Background Art

[0002] In the field of CNC tools, transition metal nitrides such as TiAlN and AlCrN have been widely used as protective coating materials. However, when processing difficult-to-cut materials, especially under high-efficiency processes such as high-speed cutting and dry cutting, the intrinsic properties of traditional nitride coatings have been difficult to adapt to the current cutting environment. In order to solve the problems of short tool life and insufficient wear resistance when cutting difficult-to-cut materials at high speed, a lot of exploration has been carried out from the perspectives of coating structure, composition and deposition parameters. It is found that by doping different elements into the coating, its microstructure can be significantly improved, thereby improving the hardness, wear resistance and high-temperature oxidation resistance of the coating. In addition, the design of the coating structure, such as the construction of superlattice coatings, is also crucial to the improvement of performance. By alternately growing different components at nanometer thickness, using the "superlattice effect" and the "modulus difference" between layers, the high hardness of the coating can be ensured, while enhancing its toughness, improving high-temperature wear resistance, and extending its service life. However, in the actual preparation process, to achieve the superlattice effect of the coating, the modulation period (i.e. the sum of the thickness of two consecutive layers) and the modulation ratio (i.e. the ratio of the thickness of two consecutive layers) must be precisely controlled, which is difficult to obtain through conventional methods. Therefore, how to efficiently and stably prepare nano multilayer coatings with superlattice effect has become a major problem.

[0003] Although physical vapor deposition (PVD) technology is currently commonly used as an advanced coating deposition method and is widely used in the industry, it has also derived a variety of technical types. Among them, high-power pulsed magnetron sputtering technology (HiPIMS) has attracted a lot of attention due to its high target ionization rate, fast deposition rate and high density of the coating during coating deposition. However, when preparing nano-multilayer coatings, HiPIMS technology makes it difficult to form a layered structure during the coating growth process due to the randomness of the movement of sputtering ions in the high vacuum chamber, which increases the difficulty of forming a superlattice structure. To overcome this problem, it is necessary to use specific process deposition parameters and target installation positions to achieve the directional movement of target ions, reduce the difficulty of nano-multilayer structure coating deposition operation, and quickly produce a tool coating structure with hardness and wear resistance that meets process requirements. Summary of the invention

[0004] The present invention aims to provide a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating and a preparation method thereof, so as to solve the problem that the existing superlattice coating is difficult to prepare, the operation is complicated, and it is difficult to ensure the stability and yield of the coating, thereby making the existing cutting tools have low hardness and low wear resistance and difficult to meet the existing process requirements.

[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating. This scheme adjusts the target installation position and the deposition time of the single-layer coating to control the modulation period and modulation ratio of the nano-multilayer coating, thereby obtaining a nano-multilayer coating with a superlattice structure, and further improving the hardness and wear resistance while ensuring that it has the performance advantages of the corresponding single-layer coating. The superlattice coating of this scheme includes a nano-multilayer coating structure, the total thickness of which is 3.7 to 5.0 μm; the nano-multilayer coating structure is composed of two face-centered cubic structures of TiAlN nanolayers and TiSiN nanolayers deposited alternately; the thickness ratio of the TiAlN nanolayer to the TiSiN nanolayer is 1:1, and the thickness of the single layer is less than 10 nm.

[0006] At the same time, the present scheme also provides a method for preparing a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating, which is applied to the above-mentioned high-hardness and wear-resistant TiAlN / TiSiN superlattice coating, including pre-treating the substrate, and after the treatment, depositing the substrate according to the set target position installation method to obtain a sample; wherein the deposition includes a substrate heating step, a substrate etching step, a target cleaning step, a nano-multilayer coating deposition step and a cooling step; the nano-multilayer coating deposition step is to use two TiAl targets and two TiSi targets for co-sputtering deposition in an Ar and N2 mixed atmosphere, and the deposition time of the single-layer coating is controlled to regulate the modulation period and modulation ratio of the multi-layer coating, wherein the deposition time of the single-layer coating is 10 to 20 seconds.

[0007] The principles and advantages of this solution are:

[0008] This scheme adjusts the modulation period and modulation ratio of the nano multilayer coating by adjusting the target installation position and the deposition time of the single layer coating. Compared with the coating prepared by DC magnetron sputtering technology, the coating structure obtained by this scheme is denser and has fewer internal defects. At the same time, the specific ion acceleration is controlled by the synchronous pulse bias power supply, which effectively avoids the gas Ar + Enter the interior of the coating, reduce coating stress, and ensure the mechanical properties of the coating.

[0009] Compared with the corresponding single-layer coating, the two different components in this scheme grow alternately at the nanometer level, which has obvious advantages. Due to the difference in modulus and lattice between different layers, the coating crystal plane slip is difficult, the grain growth is restricted, and its hardness is increased. At the same time, the nanostructure is conducive to the epitaxial growth of the coating, forming a heterogeneous coherent structure to ensure the stability of the coating. In addition, the structural characteristics of the superlattice coating limit the expansion of cracks inside the coating and improve the fracture toughness of the coating.

[0010] The preparation method of this scheme is simple, and a nano multilayer coating with a superlattice structure can be obtained, which has a high deposition rate, higher coating hardness and better wear resistance.

[0011] Furthermore, the atomic percentage of each element in the nano multilayer coating is Ti: 15% to 35%, Al: 5% to 15%, Si: 0.8% to 5%, and N: 45% to 55%.

[0012] Furthermore, the hardness of the nano multilayer coating is 37.8 GPa to 45.4 GPa; its average friction coefficient is less than 0.4, and is less than the friction coefficient of a single-layer TiAlN coating.

[0013] Furthermore, the target installation method is to place a spare target and two TiAl targets on the left side of the chamber from top to bottom, and to place another spare target and two TiSi targets on the right side of the chamber from top to bottom, so that the two spare targets, two TiAl targets and two TiSi targets are symmetrical.

[0014] Furthermore, the substrate heating step is to place the dried cemented carbide substrate into a deposition chamber and then evacuate the deposition chamber to a pressure of 2×10 -3 ~3×10 -3 Pa; set the heating temperature to 450-500°C and the heating time to 1h; set the pressure in the deposition chamber to less than 3×10 -3 ~4×10 -3 After Pa, enter the next stage.

[0015] Furthermore, the substrate etching step includes a medium frequency power supply etching stage and a direct current power supply etching stage;

[0016] The medium frequency power supply etching stage is etched for 10 minutes at an Ar gas flow rate of 250-300 sccm; the discharge parameters are set to a frequency of 240 kHz, a voltage of -650 V, and a pulse width of 1600 ns;

[0017] The DC power supply etching stage is to adjust the Ar gas flow rate to 320-420 sccm and use an ion booster to increase the etching ion concentration; the voltage of the DC power supply is -200-500V, the current of the ion booster is 20A, and the etching time is 1h.

[0018] Furthermore, the target cleaning step is to adjust the Ar gas flow rate to 450-650 sccm, close the target baffle, turn on the corresponding target power supply, set the power to 8000 W, and the cleaning time to 190-600 s.

[0019] Furthermore, the nano multilayer coating deposition step also includes maintaining the substrate temperature at 450-500°C during the deposition process; wherein the total deposition time is 7200-9000s; the Ar gas flow rate is 400-650sccm, and the N2 gas flow rate is 50-300sccm; and the cathode power supply and the bias power supply are turned on for synchronous discharge, wherein the discharge parameters of the cathode power supply are power 8000W, frequency 4000Hz, and pulse width 70μs; and the discharge parameters of the bias power supply are voltage -60V, frequency 4000Hz, and pulse width 60μs.

[0020] Furthermore, the cooling step is to cool the sample to 80-180° C. in a vacuum and then take it out after the coating deposition is completed. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention provides a schematic flow chart of a method for preparing a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating.

[0022] Figure 2 This is a top view of the interior of the chamber of the device for preparing TiAlN / TiSiN superlattice coatings of the present invention and a structural schematic diagram of the target material installation position.

[0023] Figure 3 Schematic diagram of the comparison of XRD patterns of TiAlN / TiSiN superlattice coatings in Example 1, Example 2 and Example 3 of the present invention.

[0024] Figure 4 TEM comparison of the high-magnification fracture morphology of the TiAlN / TiSiN nano multilayer coating in Example 1 of the present invention and Comparative Example 1.

[0025] Figure 5 Schematic diagram for comparing the XRD spectra of the TiAlN / TiSiN nano multilayer coatings in Comparative Example 1 and Comparative Example 2 of the present invention.

[0026] Figure 6 This is the friction coefficient curve of the TiAlN / TiSiN nano multilayer coating of Comparative Example 1 of the present invention.

[0027] Figure 7 This is the friction coefficient curve of the TiAlN single-layer coating of Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0028] The following is further described in detail through specific implementation methods:

[0029] In this embodiment, a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating is used to control the modulation period and modulation ratio of the nano-multilayer coating by adjusting the target installation position and the deposition time of the single-layer coating. The upper layer grows epitaxially under the "template effect" of the lower layer to form a superlattice coating, which further improves the hardness and wear resistance while ensuring that it has the performance advantages of the corresponding single-layer coating. In this embodiment, the total thickness of the nano-multilayer coating structure is about 3.7 to 5.0 μm. The nano-multilayer coating structure is composed of two face-centered cubic structures of TiAlN nanolayers and TiSiN nanolayers deposited alternately. Among them, the thickness ratio of the TiAlN nanolayer and the TiSiN nanolayer is approximately 1:1, and the thickness of the single layer is less than 10nm.

[0030] In this embodiment, the atomic percentages of the elements in the nano multilayer coating structure are Ti: 15% to 35%, Al: 5% to 15%, Si: 0.8% to 5%, and N: 45% to 55%. Thus, the hardness of the nano multilayer coating reaches 37.8GPa to 45.4GPa, achieving a superhard level, and its average friction coefficient is less than 0.4, which is lower than the friction coefficient of a single-layer TiAlN coating. The wear resistance of the coating is increased by coupling the superlattice structure and the amorphous phase Si3N4.

[0031] At the same time, in this embodiment, a method for preparing a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating is also provided, which is used to prepare the above-mentioned superlattice coating. Figure 1 As shown, it includes substrate pretreatment and deposition treatment.

[0032] Among them, the substrate pretreatment is carried out before the deposition treatment, including polishing, demagnetization, dry sandblasting, wet sandblasting, and ultrasonic cleaning of the substrate (including cemented carbide, metal ceramics, steel products, alumina ceramics, cermets, CBN and other superhard materials). It effectively improves the flatness and finish of the substrate, avoids interference with the substrate, improves the stability and reliability of the substrate, is conducive to subsequent coating treatment, and provides a good foundation for subsequent treatment. The specific method can be achieved by existing technical means, which will not be repeated here.

[0033] After the substrate is pretreated, the deposition process is performed according to the target installation method. Figure 2 As shown in FIG. 1 , a spare target material and two TiAl targets are arranged on the left side of the chamber from top to bottom along the chamber structure, and another spare target material and two TiSi targets are arranged on the right side of the chamber from top to bottom along the chamber structure, so that the two spare targets, two TiAl targets and two TiSi targets are symmetrical. On this basis, a deposition process is performed to obtain a sample. In this embodiment, as shown in FIG. Figure 1 As shown, the deposition process includes a substrate heating step, a substrate etching step, a target cleaning step, a nano multilayer coating deposition step, and a cooling step.

[0034] The substrate heating step includes placing the dried cemented carbide substrate on a workpiece rack and sending it into a deposition chamber, evacuating the deposition chamber, and pumping the pressure in the deposition chamber to 2×10 -3 ~3×10 -3 In this embodiment, the heating is divided into front and rear heaters, and the arrangement is as shown in the attached figure. Figure 2 As shown, the heaters are arranged at the front and back sides of the chamber. The distance between the heater and the substrate is different, so the heating power is different. The heating temperature is set to 450-500°C, and the heating time is about 1 hour. In this embodiment, after the heating is completed, the air pressure in the vacuum chamber is automatically detected every 10 minutes to ensure that the air pressure in the deposition chamber is less than 3×10 -3 ~4×10 -3 Pa before entering the next stage, that is, the substrate etching step.

[0035] In this embodiment, the substrate etching step is divided into two stages, namely the medium frequency power etching stage and the direct current power etching stage. The first stage is the medium frequency power etching stage: etching for 10 minutes at an Ar gas flow rate of 250 to 300 sccm; the discharge parameters are set to a frequency of 240kHz, a voltage of -650V, and a pulse width of 1600ns. The second stage is the direct current power etching stage: adjust the Ar gas flow rate to 320 to 420sccm, and use an ion booster to increase the etching ion concentration; the voltage of the direct current power supply is -200 to -500V, the current of the ion booster is 20A, and the etching time is 1h. Through medium frequency and direct current etching treatment to remove impurities such as surface oil stains, the bonding strength between the coating and the substrate is improved.

[0036] After the etching is completed, the target cleaning step is performed. In this embodiment, the target cleaning step is to adjust the Ar gas flow rate to 450-650 sccm, close the target baffle, and open the target baffle as shown in the attached figure. Figure 2 The four target power supplies shown in the figure, namely the cathode power supplies at four positions of two TiAl targets and two TiSi targets, are set to 8000 W, and the cleaning time is 190 to 600 s.

[0037] After cleaning, the TiAlN / TiSiN nano multilayer coating deposition step is performed. In this embodiment, it should be noted that the heater needs to be kept turned on during the entire deposition process to ensure that the substrate temperature is maintained at 450-500° C. Then, two TiAl targets and two TiSi targets are co-sputtered and deposited in an Ar and N2 mixed atmosphere. The total deposition time is 7200-9000 s, and the bias power supply is turned on for synchronous discharge.

[0038] In this embodiment, the modulation period and modulation ratio of the multilayer coating are regulated by controlling the deposition time of the single-layer coating, wherein the deposition time of the single-layer coating is 10 to 20 seconds. The Ar gas flow rate is 400 to 650 sccm, and the N2 gas flow rate is 50 to 300 sccm. The cathode power supply and bias power supply used are both high-power pulsed magnetron sputtering power supplies, wherein the discharge parameters of the cathode power supply are set to power 8000W, frequency 4000Hz, and pulse width 70μs; the discharge parameters of the bias power supply are set to voltage -60V, frequency 4000Hz, and pulse width 60μs.

[0039] After the coating deposition is completed, a cooling step is performed. In this embodiment, the cooling step is to turn off the heating power supply, cathode power supply and bias power supply, stop ventilation, allow the sample to cool in a vacuum, and take out the sample after the heating wire temperature cools to 80-180°C.

[0040] In this embodiment, wet sandblasting is also performed on the sample after the coating sample is taken out to release the internal stress of the coating, smooth the surface, and significantly reduce the roughness of the coating. Ultrasonic cleaning is performed again, and finally demagnetization is performed. Thereby improving the stability, reliability and durability of the sample.

[0041] The following is a detailed description with specific embodiments:

[0042] Example 1

[0043] In this embodiment, after the substrate is pretreated, Figure 2 The target position installation method shown in the figure is used to perform deposition processing on the substrate. In the substrate heating step, the pressure in the deposition chamber is pumped down to 3×10 -3 Pa, and the heating temperature was set to 500 °C. After heating for 1 h, the pressure in the deposition chamber was ensured to be less than 4 × 10 -3 After Pa, enter the next stage.

[0044] In the substrate etching step, in the first stage of medium frequency power etching, the Ar gas flow rate is set to 250 sccm, the etching time is 10 min, and the other parameters remain unchanged; in the second stage of DC power etching, the Ar gas flow rate is adjusted to 320 sccm, the DC power supply voltage is -200 V, and the other parameters remain unchanged.

[0045] In the target cleaning step, the Ar gas flow rate was set to 650 sccm, the power of the four target power supplies was set to 8000 W, and the cleaning time was set to 190 s.

[0046] In the nano-multilayer coating deposition step, the substrate temperature was maintained at 500°C, the total deposition time was 8100s, the Ar gas flow rate was 530sccm, the N2 gas flow rate was 300sccm, the deposition time of the single-layer coating was controlled to be 10s, and the other parameters remained unchanged.

[0047] In the cooling step, the sample was cooled to 80° C. and then taken out.

[0048] The remaining steps remain unchanged, and the prepared samples are analyzed to obtain the following Figure 3 The XRD patterns of the TiAlN / TiSiN superlattice coating are shown in FIG. Figure 4 The high-magnification fracture morphology TEM image shown. Figure 3 It can be seen from the XRD spectrum of the coating that satellite peaks appear (satellite points in the figure), indicating that the coating forms a superlattice structure. Figure 4 The TEM image of the middle coating shows that the ratio of the single layer thickness is approximately 1:1, and the single layer thickness is about 7nm. In addition, the coating hardness can reach 41.2±4.22GPa, reaching the superhard level.

[0049] Example 2

[0050] In this embodiment, what is different from that in Embodiment 1 is that in the substrate heating step, the heating temperature is set to 450° C., and the other parameters remain unchanged.

[0051] In the substrate etching step, in the first stage of medium frequency power etching, the Ar gas flow rate is set to 300 sccm, and the other parameters remain unchanged; in the second stage of DC power etching, the voltage of the DC power supply is set to -300 V, and the other parameters remain unchanged.

[0052] In the target cleaning step, the Ar gas flow rate was set to 450 sccm, the cleaning time was set to 600 s, and the other parameters remained unchanged.

[0053] In the nano-multilayer coating deposition step, the substrate temperature was maintained at 450°C, the total deposition time was 7500s, the N2 gas flow rate was 100sccm, the deposition time of the single-layer coating was controlled to be 12s, and the other parameters remained unchanged.

[0054] In the cooling step, the sample was cooled to 180° C. and then taken out.

[0055] The remaining steps remain unchanged, and the prepared samples are analyzed to obtain the following Figure 3 The XRD pattern of the TiAlN / TiSiN superlattice coating is shown in Figure 3 It can be seen that satellite peaks also appear in the XRD spectrum of the coating, indicating that the preparation steps of this embodiment can also obtain a TiAlN / TiSiN nano-multilayer coating with a superlattice structure, and the nano-hardness of the coating is 37.8±0.84 GPa, which meets the conditions for industrial use.

[0056] Example 3

[0057] In this embodiment, the difference from the first embodiment is that in the substrate heating step, the pressure of the deposition chamber is pumped down to 2×10 - 3 Pa post-heating, the heating temperature was set to 480 °C, and the pressure in the deposition chamber was ensured to be less than 3 × 10 -3 After Pa, it enters the next stage, and the other parameters remain unchanged.

[0058] In the substrate etching step, in the first stage of medium frequency power etching, the Ar gas flow rate is set to 300 sccm, and the other parameters remain unchanged; in the second stage of DC power etching, the Ar gas flow rate is adjusted to 420 sccm, and the other parameters remain unchanged.

[0059] In the target cleaning step, the Ar gas flow rate was set to 450 sccm, the cleaning time was set to 300 s, and the other parameters remained unchanged.

[0060] In the nano-multilayer coating deposition step, the substrate temperature was maintained at 480°C, the N2 gas flow rate was 350 sccm, the deposition time of the single-layer coating was controlled to be 14 s, and the other parameters remained unchanged.

[0061] In the cooling step, the sample was cooled to 120° C. and then taken out.

[0062] The remaining steps remain unchanged, and the prepared samples are analyzed to obtain the following Figure 3 The XRD pattern of the TiAlN / TiSiN superlattice coating is shown in Figure 3 It can be seen that satellite peaks appear in the XRD spectrum of the coating, indicating that under this modulation period and modulation ratio, the coating still has a superlattice structure. The coating hardness is 39.9±3.03GPa, which meets the needs of industrial production.

[0063] Comparative Example 1

[0064] This comparative example is different from Example 1 in that, in the substrate etching step, the Ar gas flow rate is set to 200 sccm in the first stage of medium frequency power etching, and the other parameters remain unchanged; the parameters of the second stage of DC power etching remain unchanged.

[0065] In the nano multilayer coating deposition step, the N2 gas flow rate was set to 400 sccm, the deposition time of the single-layer coating was controlled to 20 s, and the other parameters remained unchanged.

[0066] The remaining steps remain unchanged, and only the deposition time of the single-layer coating is changed to obtain the following Figure 5 The XRD results from Figure 5 It is found that there is no satellite peak in XRD. Figure 4The TEM image shows that the ratio of the single layer thickness is close to 1.5:1 and the modulation period is 17nm. Therefore, it is inferred that the superlattice structure cannot be formed using this deposition parameter. Figure 6 As shown, Figure 6 The horizontal axis represents the sliding time, and the vertical axis represents the friction coefficient. Figure 6 It can be seen that the average friction coefficient of the coating is about 0.3.

[0067] Comparative Example 2

[0068] This comparative example is different from Example 1 in that only one TiSi target is used in this comparative example, and the position of the TiSi target is not required.

[0069] Meanwhile, in the substrate heating step, the heating temperature was set to 480° C., and the other parameters remained unchanged.

[0070] In the substrate etching step, in the first stage of medium frequency power etching, the Ar gas flow rate is set to 200 sccm, and the other parameters remain unchanged; in the second stage of DC power etching, the parameters remain unchanged.

[0071] During the target cleaning step, the three target power supplies were turned on and the other parameters remained unchanged.

[0072] In the nano-multilayer coating deposition step, the substrate temperature was maintained at 480°C, the total deposition time was 7500s, the N2 gas flow rate was 400sccm, the deposition time of the TiAlN single-layer coating was controlled to be 20s, the deposition time of the TiSiN single-layer coating was controlled to be 10s, and the other parameters remained unchanged.

[0073] In the cooling step, the sample was cooled to 180° C. and then taken out.

[0074] The remaining steps remain unchanged, and the prepared samples are analyzed to obtain the following Figure 5 The XRD pattern of the TiAlN / TiSiN superlattice coating is shown in Figure 5 It can be seen that the XRD spectrum also does not have satellite peaks, but its own peak intensity is higher than that of Comparative Example 1, indicating better crystallinity, which is mainly caused by the thicker TiAlN layer.

[0075] Comparative Example 3

[0076] The difference between this comparative example and Example 1 is that Figure 1 The TiSi targets were all replaced with TiAl targets to obtain a single-layer TiAlN coating.

[0077] Meanwhile, in the substrate etching step, in the first stage of medium frequency power etching, the Ar gas flow rate is set to 200 sccm, and the other parameters remain unchanged; in the second stage of DC power etching, the parameters remain unchanged.

[0078] In the target cleaning step, the power of the four target power supplies was set to 12000 W, the cleaning time was set to 200 s, and the other parameters remained unchanged.

[0079] In the TiAlN single-layer coating deposition step, the total deposition time is 7200 s, the N2 gas flow rate is 550 sccm, and the other parameters remain unchanged.

[0080] In the cooling step, the sample was cooled to 180° C. and then taken out.

[0081] The remaining steps remain unchanged, and the prepared samples are analyzed to obtain the following Figure 7 The friction coefficient curve of the TiAlN single layer coating is shown in Figure 7 The horizontal axis represents the sliding time, and the vertical axis represents the friction coefficient. According to the results, the hardness of the single-layer TiAlN coating is 34.1±1.84GPa, which does not reach the super-hard level, and the average friction coefficient is about 0.6, which is relatively large.

[0082] The above examples and comparative examples show that Figure 2 The device can obtain a nano multilayer coating by controlling the deposition time of a single layer of coating. The formation of a superlattice structure requires a specific modulation period and modulation ratio. At the same time, due to the different deposition rates of TiAlN and TiSiN, it is very difficult to obtain TiAlN and TiSiN layers with the same thickness. The present invention reduces the modulation ratio to approximately 1:1 by adjusting the deposition power and the single layer deposition time, and controls the modulation period to 13nm, thereby obtaining a TiAlN / TiSiN nano multilayer coating with a superlattice structure. The hardness of the coating can exceed 40GPa, reaching a superhard level. At the same time, compared with a single layer of TiAlN coating, the superlattice coating has a lower friction coefficient and better wear resistance, and has great application potential in the field of tool cutting.

[0083] In this embodiment, the coating is composed of TiAlN and TiSiN layers of nanometer-level thickness grown alternately, which has high hardness, high fracture toughness and excellent wear resistance under the coupling effect of superlattice structure and amorphous Si3N4. The nano multilayer coating is obtained by high-power pulsed magnetron sputtering technology. The thickness of the single layer is adjusted by controlling the deposition time of the single layer coating. The prerequisite for obtaining the superlattice structure is to ensure that the thickness of the single layer is less than 10nm. The operation method of preparing the TiAlN / TiSiN superlattice coating of the present invention is simple, the deposition rate is high, the coating process is stable, and the coating structure and performance can be precisely controlled. The TiAlN / TiSiN superlattice coating obtained in this embodiment has potential application value in occasions prone to friction and wear such as tool cutting and molds.

[0084] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A high hardness and wear-resistant TiAlN / TiSiN superlattice coating, characterized in that: The invention comprises a nano multilayer coating structure, wherein the total thickness of the nano multilayer coating is 3.7 to 5.0 μm; the nano multilayer coating structure is composed of two face-centered cubic structures of TiAlN nanolayers and TiSiN nanolayers deposited alternately; the thickness ratio of the TiAlN nanolayer to the TiSiN nanolayer is 1:1, and the thickness of a single layer is less than 10 nm.

2. The high hardness and wear-resistant TiAlN / TiSiN superlattice coating according to claim 1, characterized in that: The atomic percentage of each element in the nano multi-layer coating is Ti: 15% to 35%, Al: 5% to 15%, Si: 0.8% to 5%, and N: 45% to 55%.

3. The high hardness and wear-resistant TiAlN / TiSiN superlattice coating according to claim 1, characterized in that: The hardness of the nano multilayer coating is 37.8 GPa to 45.4 GPa; Its average friction coefficient is less than 0.4, and is smaller than the friction coefficient of a single-layer TiAlN coating.

4. A method for preparing a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating, characterized in that: A high-hardness, wear-resistant TiAlN / TiSiN superlattice coating applied to any one of claims 1-3, comprising pre-treating a substrate, and after the treatment, depositing the substrate according to a set target position installation method to obtain a sample; wherein the deposition includes a substrate heating step, a substrate etching step, a target cleaning step, a nano-multilayer coating deposition step and a cooling step; the nano-multilayer coating deposition step is to use two TiAl targets and two TiSi targets for co-sputtering deposition in an Ar and N2 mixed atmosphere, and the deposition time of a single-layer coating is controlled to regulate the modulation period and modulation ratio of the multilayer coating, wherein the deposition time of a single-layer coating is 10 to 20 seconds.

5. The method for preparing a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating according to claim 4, characterized in that: The target installation method is to place a spare target and two TiAl targets on the left side of the chamber from top to bottom, and to place another spare target and two TiSi targets on the right side of the chamber from top to bottom, so that the two spare targets, two TiAl targets and two TiSi targets are symmetrical.

6. The method for preparing a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating according to claim 4, characterized in that: The substrate heating step is to place the dried cemented carbide substrate into a deposition chamber and evacuate the deposition chamber to a pressure of 2×10 -3 ~3×10 -3 Pa; set the heating temperature to 450-500°C and the heating time to 1h; set the pressure in the deposition chamber to less than 3×10 -3 ~4×10 -3 After Pa, enter the next stage.

7. The method for preparing a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating according to claim 4, characterized in that: The substrate etching step includes a medium frequency power supply etching stage and a direct current power supply etching stage; The medium frequency power etching stage is to etch for 10 minutes at an Ar gas flow rate of 250-300 sccm; Its discharge parameters are set as frequency 240kHz, voltage -650V, pulse width 1600ns; The DC power supply etching stage is to adjust the Ar gas flow rate to 320-420 sccm and use an ion booster to increase the etching ion concentration; the voltage of the DC power supply is -200-500V, the current of the ion booster is 20A, and the etching time is 1h.

8. The method for preparing a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating according to claim 4, characterized in that: The target cleaning step is to adjust the Ar gas flow rate to 450-650 sccm, close the target baffle, turn on the corresponding target power supply, set the power to 8000 W, and the cleaning time to 190-600 s.

9. The method for preparing a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating according to claim 4, characterized in that: The nano multilayer coating deposition step also includes maintaining the substrate temperature at 450-500°C during the deposition process; wherein the total deposition time is 7200-9000s; the Ar gas flow rate is 400-650sccm, and the N2 gas flow rate is 50-300sccm; and the cathode power supply and the bias power supply are turned on for synchronous discharge, wherein the discharge parameters of the cathode power supply are power 8000W, frequency 4000Hz, and pulse width 70μs; and the discharge parameters of the bias power supply are voltage -60V, frequency 4000Hz, and pulse width 60μs.

10. The method for preparing a high-hardness and wear-resistant TiAlN / TiSiN superlattice coating according to claim 4, characterized in that: The cooling step is to cool the sample to 80-180° C. in a vacuum after the coating deposition is completed and then take it out.

Citation Information

Cited By

  • Nano-composite coating for high-hardness die steel washing and milling cutter

    CN120556032A